Driving small and medium-sized enterprise participation in global value chains: Evidence from India - Ketan Reddy; Subash Sasidharan (Asian Development Bank Institute (ADBI), 2020)
In this study, we examine the participation of small and medium-sized enterprises (SMEs) in global value chains (GVCs) and highlight the role of financial constraints in shaping their participation in GVCs. We use a rich unbalanced panel of 888 SMEs for Indian manufacturing over the period 2006-2016. While examining the effect of financial constraints on the participation in GVCs of Indian SMEs, our sample suffers from two possible sources of endogeneity. In this regard, the empirical strategy employed in this study allows us to correct for reverse causality and self-selection bias. We correct for reverse causation using an instrumental variable approach and account for selection bias using a two-step probit selection model. Our findings highlight that GVC firms in the sample find financial constraints to be a significant deterring factor for Indian SMEs trying to participate in GVCs. Further, the findings of our study are robust to alternative definitions of SMEs and GVCs.
Keywords: F14; F15; L25; D24; 330; global value chains; SMEs; financial constraints; India; manufacturing